2006
DOI: 10.1093/humrep/del339
|View full text |Cite
|
Sign up to set email alerts
|

Association between endometriosis stage, lesion type, patient characteristics and severity of pelvic pain symptoms: a multivariate analysis of over 1000 patients

Abstract: The association between endometriosis stage and severity of pelvic symptoms was marginal and inconsistent and could be demonstrated only with a major increase in study power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
285
6
20

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(330 citation statements)
references
References 39 publications
19
285
6
20
Order By: Relevance
“…The above findings similar to the other evocative study proved by Vercellini, quite a number of infertility cases has reported the even mere signs and symptoms caused by endometriosis. 19 In a vast, it's been identified that endometriosis is also one of the risk factor for causing primary infertility, this were carried in hospital based case control study. According to female age to categories the infertility women in lower and higher age group were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The above findings similar to the other evocative study proved by Vercellini, quite a number of infertility cases has reported the even mere signs and symptoms caused by endometriosis. 19 In a vast, it's been identified that endometriosis is also one of the risk factor for causing primary infertility, this were carried in hospital based case control study. According to female age to categories the infertility women in lower and higher age group were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Considerado o poluente ambiental mais tóxico ao homem, o tetrachlorodibenzo-p-dioxina (TCDD) 2,3,7,8 tem sido amplamente estudado 9 . Entretanto, certos bifenilos policlorados (PCBs) apresentam toxicidade biológica similar ao TCDD e, portanto, também podem agir comprometendo a função reprodutiva.…”
unclassified
“…Estima-se que o número de mulheres com endometriose seja de 7 milhões nos Estados Unidos da América e de mais de 70 milhões no mundo. Em países industrializados, essa é uma das principais causas de hospitalização ginecológica 3 . Apesar de ser uma das doenças mais estudadas em ginecologia 4 , alguns aspectos continuam sendo alvo de pesquisa, destacando-se a busca pela sua etiopatogenia [5][6][7] .…”
unclassified
“…Delays in diagnosis may be explained by the nonspecific nature of symptoms and, in some cases, by impaired access to specialized diagnostic modalities. 8,[13][14][15][16] Furthermore, practices that may decrease exposure to estrogen, such as physical exercise and smoking, appear to confer protection 3,17 Some aspects of endometriosis are still the subject of research. Investigations have placed particular emphasis on the etiology and pathogenesis of the condition, as an understanding of the causal mechanisms behind formation of endometriotic lesions would help direct efforts towards improved diagnosis and management.…”
mentioning
confidence: 99%